Synthesis, characterization and biological evaluation of octyltrimethylammonium tetrathiotungstate - Vega-Granados, Karla; Cruz-Reyes, Juan; Horta-Marrón, José F.; Mari-Beffa, Manuel; Díaz-Rubio, Laura; Córdova-Guerrero, Iván; Chávez-Velasco, Daniel; Ocaña Farfán, María del Carmen; Medina-Torres, Miguel Ángel; Romero-Sánchez, Lilian B. (Springer Nature, 2021)
Octyltrimethylammonium tetrathiotungstate salt (ATT-C8) was synthesized and its ability to chelate copper was evaluated. The biological and toxic aspects were evaluated by in vitro and in vivo assays, using bovine aorta endothelial cells (BAEC) and zebrafish (Danio rerio) embryos. The obtained results suggest that ATT-C8 has better biocompatibility, showing a significantly lower lethal concentration 50 (LC50) value in comparison to ammonium tetrathiotungstate (ATT). Zebrafish embryos assay results indicate that both tetrathiotungstate salts at the studied concentrations increase the hatching time. Even more, an in vivo assay showed that synthesized materials behave as copper antagonists and have the ability to inhibit its toxicological effects. Also, both materials were found to be active for the in vitro 2,2-diphenyl-1-picrylhydrazyl (DPPH) assay. The characterization of the materials was carried out using the following spectroscopic techniques: Ultraviolet–Visible (UV–Vis), Fourier Transform Infrared (FTIR) and proton nuclear magnetic resonance (1H-NRM).
Keywords: Peces - Embriones; Octyltrimethylammonium tetrathiotungstate; Endothelial cells; Zebrafish; Biological activity; Copper chelator